A new species of Tricholabiodes Radoszkowski, 1885 (Hymenoptera: Mutillidae) from Saudi Arabia - Soliman, Ahmed M. (Zootaxa, 2016)
A new species, Tricholabiodes aldryhimi Soliman, sp. nov., with a posteromesal bifurcal sessile process on the third metasomal sternum is described and illustrated from Najd Region, Saudi Arabia. The new species looks like T. brothersi Lelej, 2010 in having a bifurcal process on S3 but differs from it mainly in colour and the shape of the genitalia.